A short history of mediastinal tumours - Grisbolaki, Evaggelia; Leivaditis, Vasileios; Grapatsas, Konstantinos; Koletsis, Efstratios; Mulita, Francesk; Flouri, Maria; Gravanis, Dimos; Vakis, Georgios; Panagiotopoulos, Ioannis; Dahm, Manfred; Verras, Georgios-Ioannis; Tasios, Konstantinos; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2023)
The mediastinum constitutes an area of special surgical interest due to important anatomical relationships and histopathologic variability of mediastinal primary and metastatic tumours. Mediastinum was considered inaccessible until the end of the 19th century. For many decades the diagnosis of mediastinal disease relied solely upon clinical presentation, and the mainstay of treatment was medical therapy. The advancements in radiology and intraoperative ventilatory support facilitated the improvement of certain diagnostic and therapeutic approaches to mediastinal disease.